High quality DNA isolation in Psidium guajava L. for genomic studies - Sánchez-Barrantes, Elodia (2021)
Introduction. Guava is one of the main fruit trees of the Myrtaceae family for its high nutritional value. It is originally from tropical America and the main producing countries are: Mexico, India, Brazil, and Thailand. The interest generated in recent years by the genetic improvement of this crop, has led to the use of molecular tools that allow determining genetic variability and selecting genes of agronomic interest in a fast and reliable way. However, the isolation of high-purity DNA is a prerequisite for the use of state-of-the-art molecular techniques for genetic analysis. Objective. Isolate high-quality genomic DNA (gDNA) from guava, in adequate quantity and integrity. Materials and methods. The experiment was carried out in the Molecular Biology Laboratory of the Estacion Experimental Agricola Fabio Baudrit Moreno, between January and December 2019. Three different methods for isolating DNA were compared: Promega (ReliaPrepª gDNA Tissue Miniprep Kit), Qiagen (DNeasy Plant Mini Kit), and CTAB (Doyle and Doyle, 1990) with modifications. For the gDNA extraction, fresh and lyophilized of young leaves of guava (Psidium guajava L; 2n = 22) were used. To determine the best method, the quality, quantity, and integrity of the gDNA were measured for each method. Results. The gDNA was obtained with the three evaluated methods. The best results in terms of gDNA quantity (ng µl-1) were obtained with the lyophilized material and with the CTAB method (Doyle and Doyle). The CTAB (Doyle and Doyle) and Qiagen methods showed a higher degree of purity (A260 / 280 ratios with optimal values) compared to the Promega method. Conclusion. The gDNA was obtained in adequate quantity, quality, and integrity. This was achieved based on extractions in lyophilized young leaf tissue and with the extraction method of the Qiagen kit.